Teaching Strategies for the course EIF-203 Discrete Structures for Computer Sciences through the use of the Facebook and Twitter social networks - Vílchez Quesada, Enrique (2014)
This paper is the result of the teaching research project ascribed to the School of Computer Sciences from Universidad Nacional de Costa Rica (UNA), entitled “Facebook as a Teaching and Learning Tool for the Course EIF-203 Discrete Structures for Computer Sciences through the Use of Interactive Books”. The overall objective of the project was to analyze the Facebook social network as a teaching and learning environment from a technical and pedagogical point of view. A number of teaching strategies are presented in this paper, which were created to complement the teaching of the EIF -203 course, using the Facebook and Twitter social networks as an educational platform. Shared strategies constitute an intensive search for new methodologies to enhance the teaching and ideally the learning processes in the EIF -203 course, which is part of the curriculum of the Computer Engineering Program at UNA. These strategies were implemented in a group of 31 students from the Alajuela Campus during the first semester of 2013. This permitted the evaluation of the teaching strategies developed using a quantitative methodology. The instrument used (a questionnaire) was validated by a “Cronbach’s Alpha” reliability test using a sample of 65 participants. The results are part of the analysis presented in this paper.